Tata Kelola Dana Desa yang Efektif: Studi tentang Transparansi, Akuntabilitas, Kompetensi, dan Komitmen Pemerintah Desa di Kecamatan Jetis Kabupaten Ponorogo - Nihaya Nur Arifah; Ardyan Firdausi Mustoffa; Nurul Hidayah (JAPP: JURNAL AKUNTANSI, PERPAJAKAN DAN PORTOFOLIO, 2026)
This observe aims to determine the impact of transparency, accountability, competence of village apparatus, and commitment of village government organizations at the management of village budget in villages in Jetis District, Ponorogo Regency. This study uses primary information acquired from distributing questionnaires to fourteen villages in Jetis District, Ponorogo Regency. The populace on this observe had been all village apparatus in Jetis District, Ponorogo Regency as many as 205 human beings. The sample in this examine amounted to 70 village apparatus taken via purposive sampling method. The data analysis technique used is multiple linear regression analysis with the assist of the SPSS program. The outcomes confirmed that in part and simultaneously transparency, accountability, competence of village apparatus, and organizational commitment had a positive and significant impact on the management of village budget. which means the higher level of transparency, responsibility, competence of the village apparatus, and the commitment of village government organizations, the control of village finances will be higher.